Kontrol Diri Dengan Perilaku Konsumtif Pada Dewasa Awal - Puspitasari, Rahmah Putri; Mufidah, Wardatul; Faizah, Nur; Nursanti, Erma (IDEA: Jurnal Psikologi, 2025)
This research aims to determine the relationship between self control and consumer behavior in early adults who are already working. This research involved early adults whose status is already working are 60 people aged 20-30 years old. The data collection technique was carried out online using Google Form using purposive random sampling technique. The method used for data analysis is Karl Pearson Product Moment correlation. The analysis results show a correlation coefficient of rxy = - 0.703 with Sig. 0.000 (p<0.05). The hypothesis in this research is accepted by the existence of a significant negative relationship between self-control and consumer behavior.